Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review - G. Vo Van Regnault; M. C. Costa; A. Adanić Pajić; A. P. Bico; S. Bischofova; U. Blaznik; F. Menniti-Ippolito; K. Pilegaard; C. Rodrigues; I. Margaritis (Critical Reviews in Food Science and Nutrition, 2022)

PGC-1α in exercise and fasting-induced regulation of hepatic UPR in mice - Caroline M. Kristensen; Mette A. Olsen; Henrik Jessen; Nina Brandt; Jacob N. Meldgaard; Henriette Pilegaard (Pflügers Archiv - European Journal of Physiology, 2018)

Interannual variability of net ecosystem productivity in forests is explained by carbon flux phenology in autumn - Chaoyang Wu; Jing M. Chen; T. Andrew Black; David T. Price; Werner A. Kurz; Ankur R. Desai; Alemu Gonsamo; Rachhpal S. Jassal; Christopher M. Gough; Gil Bohrer; Danilo Dragoni; Mathias Herbst; et al. (Global Ecology and Biogeography, 2013)
Aim To investigate the importance of autumn phenology in controlling interannual variability of forest net ecosystem productivity ( NEP ) and to derive new phenological metrics to explain the interannual variability of NEP . Location N orth A merica and E urope. Method Flux data from nine deciduous broadleaf forests ( DBF ) and 13 evergreen needleleaf forests ( ENF ) across N orth A merica and E urope (212 site‐years) were used to explore the relationships between the yearly anomalies of annual NEP and several carbon flux based phenological indicators, including the onset/end of the growing season, onset/end of the carbon uptake period, the spring lag (time interval between the onset of growing season and carbon uptake period) and the autumn lag (time interval between the end of the carbon uptake period and the growing season). Meteorological variables, including global shortwave radiation, air temperature, soil temperature, soil water content and precipitation, were also used to explain the phenological variations. Results We found that interannual variability of NEP can be largely explained by autumn phenology, i.e. the autumn lag. While variation in neither annual gross primary productivity ( GPP ) nor in annual ecosystem respiration ( R e ) alone could explain this variability, the negative relationship between annual NEP and autumn lag was due to a larger R e / GPP ratio in years with a prolonged autumn lag. For DBF sites, a longer autumn lag coincided with a significant decrease in annual GPP but showed no correlation with annual R e . However, annual GPP was insensitive to a longer autumn lag in ENF sites but annual R e increased significantly. Main conclusions These results demonstrate that autumn phenology plays a more direct role than spring phenology in regulating interannual variability of annual NEP . In particular, the importance of respiration may be potentially underestimated in deriving phenological indicators.

Reduction of ecosystem productivity and respiration during the European summer 2003 climate anomaly: a joint flux tower, remote sensing and modelling analysis - M. REICHSTEIN; P. CIAIS; D. PAPALE; R. VALENTINI; S. RUNNING; N. VIOVY; W. CRAMER; A. GRANIER; J. OGÉE; V. ALLARD; M. AUBINET; Chr. BERNHOFER; et al. (Global Change Biology, 2007)
The European CARBOEUROPE/FLUXNET monitoring sites, spatial remote sensing observations via the EOS‐MODIS sensor and ecosystem modelling provide independent and complementary views on the effect of the 2003 heatwave on the European biosphere's productivity and carbon balance. In our analysis, these data streams consistently demonstrate a strong negative anomaly of the primary productivity during the summer of 2003. FLUXNET eddy‐covariance data indicate that the drop in productivity was not primarily caused by high temperatures (‘heat stress’) but rather by limitation of water (drought stress) and that, contrary to the classical expectation about a heat wave, not only gross primary productivity but also ecosystem respiration declined by up to more than to 80 gC m −2 month −1 . Anomalies of carbon and water fluxes were strongly correlated. While there are large between‐site differences in water‐use efficiency (WUE, 1–6 kg C kg −1 H 2 O) here defined as gross carbon uptake divided by evapotranspiration (WUE=GPP/ET), the year‐to‐year changes in WUE were small ( −1 ) and quite similar for most sites (i.e. WUE decreased during the year of the heatwave). Remote sensing data from MODIS and AVHRR both indicate a strong negative anomaly of the fraction of absorbed photosynthetically active radiation in summer 2003, at more than five standard deviations of the previous years. The spatial differentiation of this anomaly follows climatic and land‐use patterns: Largest anomalies occur in the centre of the meteorological anomaly (central Western Europe) and in areas dominated by crops or grassland. A preliminary model intercomparison along a gradient from data‐oriented models to process‐oriented models indicates that all approaches are similarly describing the spatial pattern of ecosystem sensitivity to the climatic 2003 event with major exceptions in the Alps and parts of Eastern Europe, but differed with respect to their interannual variability.

An 18-month follow-up study on vibrotactile sense, muscle strength and symptoms in computer users with and without symptoms - M. Pilegaard; B. R. Jensen (International Archives of Occupational and Environmental Health, 2005)

Vibrotactile sense and mechanical functional state of the arm and hand among computer users compared with a control group - Jensen B.; Pilegaard M.; Momsen A. (International Archives of Occupational and Environmental Health, 2002)

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

Consistency of motor-unit identification during force-varying static contractions - M. Pilegaard; B. R. Jensen; G. Sjgaard; K. Sgaard (European Journal of Applied Physiology, 2000)

Motor unit recruitment and rate coding in response to fatiguing shoulder abductions and subsequent recovery - B. R. Jensen; M. Pilegaard; G. Sjøgaard (European Journal of Applied Physiology, 2000)